2019
DOI: 10.1101/622647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRZ1 regulator and calcium cooperatively modulate holocellulases gene expression in Trichoderma reesei QM6a

Abstract: AbstractBackgroundTrichoderma reesei is the main filamentous fungus used in industry to produce cellulases. Over the last decades, there have been a strong increase in the understanding of the regulatory network controlling cellulase-coding gene expression in response to a number of inducers and environmental signals. In this sense, the role of calcium and the Calcineurin-responsive protein (CRZ1) has been investigat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Increased concentrations of the second messenger Ca 2+ in the cytosol lead to a response in the downstream calcium pathway (Li et al 2019;Liu et al 2019). Crz1, a critical activator of the calcium signal transduction terminal, plays an essential role in calcium signal transduction pathways (Chen et al 2016;Martins-Santana et al 2020). The transcription level of the transcriptional regulator crz1 detected using RT-qPCR was upregulated after Sr 2+ induction (Fig.…”
Section: Cytosolic Ca 2+ Accumulation In T Reesei Was Induced By High...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased concentrations of the second messenger Ca 2+ in the cytosol lead to a response in the downstream calcium pathway (Li et al 2019;Liu et al 2019). Crz1, a critical activator of the calcium signal transduction terminal, plays an essential role in calcium signal transduction pathways (Chen et al 2016;Martins-Santana et al 2020). The transcription level of the transcriptional regulator crz1 detected using RT-qPCR was upregulated after Sr 2+ induction (Fig.…”
Section: Cytosolic Ca 2+ Accumulation In T Reesei Was Induced By High...mentioning
confidence: 99%
“…The intracellular calcium signaling components include free Ca 2+ , calmodulin (CaM), calcineurin (CnA), and calcineurin-responsive zinc finger transcription factor 1 (Crz1) (Bootman et al 2002). Increases in cytosolic Ca 2+ levels lead to the activation of Crz1 via Ca 2+ /CaM/ CnA, which activates downstream genes with different functions by binding to their promoter regions (Martins-Santana et al 2020). Chen et al (2016) reported that the cytosolic Ca 2+ concentration activates the binding of the transcription factor Crz1 to the cellulase gene cbh1 and main transcriptional activator of cellulase genes xyr1, thereby upregulating cellulase gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to archetypical GAL4 transcription factor in yeast, CLR-1, CLR-2, and XYR1 are members of the Zn(II) 2 Cys 6 family of transcription factors having binuclear Zn-Cys binuclear cluster-type DNA-binding domain and activators of genes of secondary carbon sources. Beside these, homologs of ACE3, BGL-R, CRZ1, VIB1, etc., have also been identified as transcriptional activators of lignocellulase in filamentous fungi 15,[18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%